Healthcare System with Intrusion Detection and Privacy Protection based Cloudlet - Dubey, Kavita V; Lomte, Vina M (International Journal of Computer Sciences and Engineering, 2018)
An individual's medical record is a vital form that can be used to track patient data accurately, reliably and completely. For all purposes, the exchange of repair information is a basic and test problem. Consequently, in this document, we develop a new structure for human services through the use of cloudlet adaptability. Cloudlet elements include security insurance, information exchange, and breakpoint location. In the information accumulation phase, we initially used the Numerical Theory Research Unit (NTRU) technique to encode client body information collected from a portable device. This information will be send to near cloudlets in a competent form of vitality. In addition, we show another model of trust to allow customers to choose trusted partners who want to share data stored in the cloudlet. The demonstration of trust also makes comparable patients who talk to each other about their illnesses. Third, we isolate the patient's medical information stored at a distance in three sections and provide them with adequate insurance.